The Effect of Service Quality on Customer Satisfaction, Customer Loyalty, and Customer Engagement for Private Bank Customers in Tangerang - Isnaini Nur Safitri; Unik Dwi Lestari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Service quality can be defined as how far the difference between reality and customer expectations of the service they receive. With the current development of banking, service quality is a key factor that will become a competitive advantage in the banking world. Based on the test results of this study, it is known that service quality has a positive effect on customer satisfaction, and service quality has a positive effect on customer engagement which plays an important role in a service at the Bank. Then, customer satisfaction has a positive effect on customer loyalty. Service quality does not have a positive effect on customer loyalty, because the influence of service quality is not enough to make customers feel loyal